2021
DOI: 10.1007/s00426-021-01498-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in vocal emotion recognition: a behavioural and skin conductance study in Portugal and Guinea-Bissau

Abstract: Cross-cultural studies of emotion recognition in nonverbal vocalizations not only support the universality hypothesis for its innate features, but also an in-group advantage for culture-dependent features. Nevertheless, in such studies, differences in socio-economic-educational status have not always been accounted for, with idiomatic translation of emotional concepts being a limitation, and the underlying psychophysiological mechanisms still un-researched. We set out to investigate whether native residents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Vocal expression of emotion is necessary for social interaction across civilizations. [1][2][3] In addition to facial expressions, people often use prosodic vocal cues to show their emotions. 4 Consequently, when prosodic vocal cues are absent, the expression and perception of emotion are hindered, negatively affecting social interactions and development.…”
Section: Introductionmentioning
confidence: 99%
“…Vocal expression of emotion is necessary for social interaction across civilizations. [1][2][3] In addition to facial expressions, people often use prosodic vocal cues to show their emotions. 4 Consequently, when prosodic vocal cues are absent, the expression and perception of emotion are hindered, negatively affecting social interactions and development.…”
Section: Introductionmentioning
confidence: 99%
“…Skin conductance response . It has been shown that emotional content increases autonomic activity, reflected in different physiological responses [ 77 , 78 ]. Electrodermal activity (EDA) is the umbrella term that refers to autonomic changes in the electrical properties of the skin [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, to the best of our knowledge, the temporal profile of IN-OT is still unexamined in the peripheral nervous system at rest. Such examination is of crucial importance for neuroscience studies’ design and interpretation because the autonomic nervous system (ANS) activity is associated with a myriad of social cognitive processes ( Jáuregui et al, 2011 ; Quintana et al, 2012 ), as we have recently shown for cognitive empathy ( Cosme et al, 2021 , 2022 ). The ANS is also more easily accessible than the central nervous system in humans.…”
Section: Introductionmentioning
confidence: 99%